2019
DOI: 10.1029/2019jg005064
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Gradients in Tree Stem Greenhouse Gas Concentrations Across Six Pacific Northwest Coastal Forests

Abstract: The aim of this study was to examine the magnitude of greenhouse gas (GHG) concentrations in tree stems of Pacific Northwest, USA coastal forests and evaluate various tree and site characteristics along river‐to‐sea gradients as possible drivers of tree stem GHG variation. We measured the concentration of CH4, CO2, and N2O during summer and winter in live and dead tree stems of five species from six coastal watersheds and related this to soil porewater GHG concentrations, porewater salinity, and tree character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 66 publications
(120 reference statements)
2
15
0
Order By: Relevance
“…Similar to patterns in C thermodynamic favorability, C compound classes showed significant heterogeneity in shallow soils but had conserved characteristics in deeper soils. The lipid-like peaks observed in the shallow floodplain samples suggest marine-associated algae-derived lipid organic matter similar to results observed by Ward et al (2019b) in a coastal wetland setting. In contrast, lignin-like signatures in the upland site suggest terrestrially derived OM, as has been observed in other environments where terrestrially derived organic molecules have a high abundance of vascular-plantderived material such as lignin (Hedges and Oades, 1997;Ward et al, 2013).…”
Section: Compound-class Landscape Gradients Suggest Influences Of Spasupporting
confidence: 83%
See 1 more Smart Citation
“…Similar to patterns in C thermodynamic favorability, C compound classes showed significant heterogeneity in shallow soils but had conserved characteristics in deeper soils. The lipid-like peaks observed in the shallow floodplain samples suggest marine-associated algae-derived lipid organic matter similar to results observed by Ward et al (2019b) in a coastal wetland setting. In contrast, lignin-like signatures in the upland site suggest terrestrially derived OM, as has been observed in other environments where terrestrially derived organic molecules have a high abundance of vascular-plantderived material such as lignin (Hedges and Oades, 1997;Ward et al, 2013).…”
Section: Compound-class Landscape Gradients Suggest Influences Of Spasupporting
confidence: 83%
“…Our fourth hypothesis is based on the observation that soils in saturated environments like floodplains are expected to be less oxygenated and can also receive deposition of marine-or algae-derived OM and suspended sediments during tidal flooding. These factors can result in OM having lower oxygen-to-carbon (O/C) and higher hydrogento-carbon (H/C) ratios as compared to upland soils (Seidel et al, 2016;Tfaily et al, 2014;Ward et al, 2019b). We therefore hypothesize a greater relative abundance of lipid-and protein-like and less lignin-and tannin-like compounds in the floodplain soils, relative to upland (i.e., drained) soil.…”
Section: Introductionmentioning
confidence: 97%
“…The mechanisms behind salinization of tidal river systems and the adjacent terrestrial environments may be unique from the comparatively well-studied freshwater wetland salinization (Ensign & Noe, 2018). Salinization impacts not only biogeochemical cycling (Ward et al, 2019) but also coastal freshwater ecosystem function, including tree health (Wang et al, 2019). Understanding the mechanisms behind seawater inundation and floodplain salinization in coastal ecosystems is therefore necessary to elucidate how such chronic salinity exposure arises, persists, and is incorporated into predictive modeling efforts needed for projecting future change.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations are available on N 2 O emissions from tree stems in laboratory 46,47 , using in situ manual stem chambers [48][49][50][51][52]38,28 and automated chambers 53 . The studies demonstrate that N 2 O can be emitted or consumed by stems whereas ooding signi cantly but only temporarily increases emissions 46,47,38,28 , especially from the lower parts of stems 38,28 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found evidence that N 2 O emitted from tree stems may originate from the soil 49 . However, no study has quanti ed the contribution of N 2 O uxes from stems in the N 2 O budget of a forest ecosystem and moreover, factors controlling N 2 O uxes from stems remain unclear 52 . It seems that N 2 O exchange from boreal tree stems might follow the tree physiological activity, especially the processes connected to CO 2 exchange 51 .…”
Section: Introductionmentioning
confidence: 99%